Production of antibodies and antibody fragments containing non-natural amino acids in Escherichia coli - Jacquelyn Blake-Hedges; Dan Groff; Wilson Foo; Jeffrey Hanson; Elenor Castillo; Miao Wen; Diana Cheung; Mary Rose Masikat; Jian Lu; Young Park; Nina Abi Carlos; Hans Usman; et al. (mAbs)
Therapeutic bioconjugates are emerging as an essential tool to combat human disease. Site-specific conjugation technologies are widely recognized as the optimal approach for producing homogeneous drug products. Non-natural amino acid (nnAA) incorporation allows the introduction of bioconjugation handles at genetically defined locations. Escherichia coli (E. coli) is a facile host for therapeutic nnAA protein synthesis because it can stably replicate plasmids encoding genes for product and nnAA incorporation. Here, we demonstrate that by engineering E. coli to incorporate high levels of nnAAs, it is feasible to produce nnAA-containing antibody fragments and full-length immunoglobulin Gs (IgGs) in the cytoplasm of E. coli. Using high-density fermentation, it was possible to produce both of these types of molecules with site-specifically incorporated nnAAs at titers > 1 g/L. We anticipate this strategy will help simplify the production and manufacture of promising antibody therapeutics.